2013
DOI: 10.3906/kim-1210-62
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Henry reaction catalyzed by Cu(I)-based chiral amino alcohol complex

Abstract: The Cu(I)-based complex prepared from (S)-2-(furan-2-yl-methylamino)-2-phenylethanol (5c) and CuCl was used as catalyst in enantioselective Henry reactions of arylaldehydes and nitromethane, which gave 89% ee and 95% yield at ambient temperature. The proposed catalytic cycle of an asymmetric Henry reaction was suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The intermediate B then reacted with the triethylammonium acetate generated earlier to obtain the corresponding β-nitroalcohol product, and at the same time, a bivalent metal complex and a triethylamine molecule were released. According to the above experimental results and the reported literature [37][38][39], we managed to deduce the possible reaction mechanism of nitromethane with aromatic aldehydes in the presence of [ML(CH 3 COO) 2 (H 2 O) n ] (n = 1, M = Ni; n = 0, M = Zn) with 20 mol% Et 3 N as the co-catalyst. As shown in Figure 6, under the action of alkaline triethylamine, nitromethane was activated to coordinate to the bivalent metal cation in [ML(CH 3 COO) 2 (H 2 O) n ], presenting a metal complex intermediate A and a triethylammonium acetate.…”
Section: Expansion Of the Substrate Scope On The Henry Reactionmentioning
confidence: 91%
“…The intermediate B then reacted with the triethylammonium acetate generated earlier to obtain the corresponding β-nitroalcohol product, and at the same time, a bivalent metal complex and a triethylamine molecule were released. According to the above experimental results and the reported literature [37][38][39], we managed to deduce the possible reaction mechanism of nitromethane with aromatic aldehydes in the presence of [ML(CH 3 COO) 2 (H 2 O) n ] (n = 1, M = Ni; n = 0, M = Zn) with 20 mol% Et 3 N as the co-catalyst. As shown in Figure 6, under the action of alkaline triethylamine, nitromethane was activated to coordinate to the bivalent metal cation in [ML(CH 3 COO) 2 (H 2 O) n ], presenting a metal complex intermediate A and a triethylammonium acetate.…”
Section: Expansion Of the Substrate Scope On The Henry Reactionmentioning
confidence: 91%
“…[103] Zhou developed the first asymmetric form of the Henry reaction by using the Cu-Schiff base complex to resolve these drawbacks. [104] In 2011, Ozturk [105] synthesized a chiral complex of Schiff base ligand 127 based on ferrocene under microwave treatment and solvent-free green chemistry approaches (Scheme 30). They found that the ferrocene carbaldehyde 125 readily responded with the different chiral amines 126 and amino alcohols in ethanol solvent in the presence of copper triflate (source of metal ion) to provide chiral Schiff base 127 (Scheme 31) in 40 h in the presence of CH 2 Cl 2 , thus, giving enantioselectivity of about 95 % ee.…”
Section: Chemistryselectmentioning
confidence: 99%